RNA Viruses, Toll-Like Receptors, and Cytokines: The Perfect Storm? - Sophia K. Stegeman; Olena Kourko; Heather Amsden; Isabella E. Pellizzari Delano; John E. Mamatis; Madison Roth; Che C. Colpitts; Katrina Gee (Journal of Innate Immunity)
Background: The interactions between viruses and the host immune response are nuanced and intricate. The cytokine response arguably plays a central role in dictating the outcome of virus infection, balancing inflammation, and healing, which is crucial to resolving infection without destructive immunopathologies. Summary: Early innate immune responses are key to the generation of a beneficial or detrimental immune response. These initial responses are regulated by a plethora of surface bound, endosomal, and cytoplasmic innate immune receptors known as pattern recognition receptors. Of these, the Toll-like receptors (TLRs) play an important role in the induction of cytokines during virus infection. Recognizing pathogen-associated molecular patterns (PAMPs) such as viral proteins and/or nucleotide sequences, the TLRs act as sentinels for the initiation and propagation of immune responses. Key Messages: TLRs are important receptors for initiating the innate response to single-stranded RNA (ssRNA) viruses like influenza A virus (IAV), severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1), SARS-CoV-2, Middle East respiratory syndrome coronavirus, dengue virus, and Ebola virus. Infection with these viruses is also associated with aberrant expression of proinflammatory cytokines that contribute to a harmful cytokine storm response. Herein we discuss the connections between these ssRNA viruses, cytokine storm, and the roles of TLRs. Background: The interactions between viruses and the host immune response are nuanced and intricate. The cytokine response arguably plays a central role in dictating the outcome of virus infection, balancing inflammation, and healing, which is crucial to resolving infection without destructive immunopathologies. Summary: Early innate immune responses are key to the generation of a beneficial or detrimental immune response. These initial responses are regulated by a plethora of surface bound, endosomal, and cytoplasmic innate immune receptors known as pattern recognition receptors. Of these, the Toll-like receptors (TLRs) play an important role in the induction of cytokines during virus infection. Recognizing pathogen-associated molecular patterns (PAMPs) such as viral proteins and/or nucleotide sequences, the TLRs act as sentinels for the initiation and propagation of immune responses. Key Messages: TLRs are important receptors for initiating the innate response to single-stranded RNA (ssRNA) viruses like influenza A virus (IAV), severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1), SARS-CoV-2, Middle East respiratory syndrome coronavirus, dengue virus, and Ebola virus. Infection with these viruses is also associated with aberrant expression of proinflammatory cytokines that contribute to a harmful cytokine storm response. Herein we discuss the connections between these ssRNA viruses, cytokine storm, and the roles of TLRs.